The term politics reconsidered in the light of recent theoretical developments - Valeri Modebadze (IBSU Scientific Journal (IBSUSJ), 2010)
This article deals with the problems of the definition of the term politics. The definition of politics varies from time to time and from place to place. In other words politics is a loaded term. It has a wide range of meanings when used in everyday life. Politics is defined in such different ways: as the study of conflict resolution, the art of government, the conduct and management of public affairs, and so on. The aim of this article is to explain the difficulties of defining the term politics. This research is based on the comparative method: two contradictory approaches to understanding politics are compared with each other, the narrow definition of politics and the broad definition of politics. The narrow definition of politics is a highly restricted understanding of politics. According to the narrow definition, politics is what takes place within the government and state departments: only politicians, government officials, members of the political parties are involved in politics. In contrast to the narrow definition of politics, broader conception of politics argues that politics is not only confined to a particular sphere, but also takes place in all aspects of human life. The problem of the definition of politics is closely linked with these two contradictory approaches to understanding politics.
Keywords: 330; politics; definition of politics; broad conceptions of politics; narrow conceptions of politics